2020
DOI: 10.4102/sajhivmed.v21i1.1154
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and spectrum of mucocutaneous disease in South African people living with HIV and accessing care at a district-level hospital

Abstract: Background: Although the association between human immunodeficiency virus (HIV) and mucocutaneous diseases has been well studied within South African specialist centres, there is limited data from district-level hospitals. Available data may, therefore, fail to reflect the prevalence and full spectrum of dermatoses seen in people living with HIV (PLWH).Objectives: To determine the prevalence and spectrum of dermatoses seen in PLWH.Method: We conducted a cross-sectional, descriptive study of 970 PLWH (men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…Toxidermia was observed in 7 (3.10%) patients among our study population, with benign drug eruptions accounting for 6 of these toxidermia cases. Our result is close to those reported in South Africa by Claasens [ 25 ]. However, Asian studies in the ART era have reported higher prevalence rates for drug eruptions, ranging from 10% to 17% [ 6 , 9 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Toxidermia was observed in 7 (3.10%) patients among our study population, with benign drug eruptions accounting for 6 of these toxidermia cases. Our result is close to those reported in South Africa by Claasens [ 25 ]. However, Asian studies in the ART era have reported higher prevalence rates for drug eruptions, ranging from 10% to 17% [ 6 , 9 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among 231 dermatological diagnoses, seborrheic dermatitis was found to be the most prevalent of noninfectious dermatoses, presented by 27 (11.73%) patients. Our result is consistent with the findings reported by Claasens et al [25] in South Africa. A high frequency of seborrheic dermatitis (40%-80%) associated with HIV infection was reported before the use of highly active ART [26].…”
Section: Principal Findingssupporting
confidence: 94%